Speech by D.Y.M.M Tuanku Syed Sirajuddin Ibni Al-Marhum Tuanku Syed Putra Jamalullail, the chancellor of USM, at the 39th convocation ceremony on 25 march 2009, at 9.00am in Dewan Tuanku Syed Putra Usm Pulau Pinang. - Tuanku Syed Putra Jamalullail, Tuanku Syed Sirajuddin (2009)

(untitled)
Bism illah i rra h man i rra him Assalamualaikum warahmatullahi wabarakatuh By grace of Allah, I am here at USM 391 h Convocation Ceremony. Congratulations to all graduates. I would also like to congratulate Dr. Concepcion Campa Huergo, recipient of the Honorary Degree of Doctor of Science this morning, whom I believed, is an excellent example of those who are committed to knowledge and contributed significantlay to the society.